Tolerance, regulation and rescue : Dishonoured women and abandoned children in Italy, 1300-1800 - Pullan, Brian S. (Book collections on Project MUSE., 2016)
This book provides a wide-ranging analysis of 'unrespectable' women and children living on the margins of mainstream Italian society, considering the interrelated aspects of Italian social history, Catholic charity and social policy over a period of five centuries.